(untitled) (European Journal of Education and Psychology, 2015)
This study evaluated the influence of gender and intelligence in early maths performance, and detected students at risk of maths learning difficulties. A total of 44 second-year preschool boys and girls (Mean age = 53.75 months) were assessed by 3 different tests: Utrecht Early Numeracy Test (UENT), the Test for the Diagnosis of Basic Skills in Mathematics (TEDI-MATH), and Raven’s Progressive Matrices Test. The results found that children with a higher IQ also had higher maths scores. However, no significant differences were found in terms of gender and intelligence, or gender and maths performance.